IMPLEMENTATION OF COOPERATIVE LEARNING MODEL STUDENT TEAMS-ACHIEVEMENT DIVISION (STAD) TYPE TO IMPROVE STUDENT COOPERATION IN SOCIAL SCIENCE LEARNING (Classroom Action Research Class VII-D SMP Negeri 1 Bandung) - Yuliawati, Dessy (Universitas Pendidikan Indonesia, 2017)
Abstract-This study is motivated by the author’s curiosity towards the effectiveness of Cooperative Learning Model Student Teams Achievement Division (STAD) type in improving student cooperation. The purpose of this study is to implementate the Cooperative Learning model Student Teams-Achievement Division (STAD) type to improve student cooperation that includes teamwork in solving problem and doing task, sharing ideas, asking and answering questions, interpersonal communication among students, students and teacher, students and informant, as well as respect for gender, ethnic, race, religion, socioeconomic status, culture and perspective differences. Classroom Action Research (PTK) uses a spiral model by Kemmis and Mc Taggart conducted in three cycles. The subjects of the study are the students of class VII-D. The implementation of learning to improve student cooperation is by implementing the Cooperative Learning model Student Teams-Achievement Division (STAD) Type in Social Science learning. Over three cycles have consistent improvements. In the first cycle, the observation on student cooperation is in the